The Unfalsifiability of Security Claims - Herley, Cormac (Proceedings of the 3rd Asian Symposium on Programming Languages and Systems (APLAS '05), 2016)
There is an inherent asymmetry in computer security: things can be declared insecure by observation, but not the reverse. There is no observation that allows us to declare an arbitrary system or technique secure. We show that this implies that claims of necessary conditions for security (and sucient conditions for insecurity) are unfalsifiable. This in turn implies an asymmetry in self-correction: while the claim that countermeasures are sucient is always subject to correction, the claim that they are necessary is not. Thus, the response to new information can only be to ratchet upward: newly observed or speculated attack capabilities can argue a countermeasure in, but no possible observation argues one out. Further, when justifications are unfalsifiable, deciding the relative importance of defensive measures reduces to a subjective comparison of assumptions. Relying on such claims is the source of two problems: once we go wrong we stay wrong and errors accumulate, and we have no systematic way to rank or prioritize measures.